2013
DOI: 10.1017/jfm.2013.495
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic flame propagation in premixed combustion

Abstract: In experiments of hot surface ignition and subsequent flame propagation, a puffing flame instability is observed in mixtures that are stagnant and premixed prior to ignition. By varying the size of the hot surface, power input, and combustion vessel volume, it was determined that the instability is a function of the interaction of the flame, with the fluid flow induced by the combustion products rather than the initial plume established by the hot surface. Pressure ranges from 25 to 100 kPa and mixtures of n-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…The present study focuses on a stationary localized surface with an imposed heating rate. Similar configurations were studied by Roth et al [7,8], Beyer and Markus [9], Dubaniewicz [10], Dubaniewicz et al [11], Dubaniewicz et al [3], Bothe et al [12], Homan [13], Boettcher et al [14], Boettcher [15], and Menon et al [16]. These previous studies demonstrated the importance of the mixture chemical properties and surface properties (e.g.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The present study focuses on a stationary localized surface with an imposed heating rate. Similar configurations were studied by Roth et al [7,8], Beyer and Markus [9], Dubaniewicz [10], Dubaniewicz et al [11], Dubaniewicz et al [3], Bothe et al [12], Homan [13], Boettcher et al [14], Boettcher [15], and Menon et al [16]. These previous studies demonstrated the importance of the mixture chemical properties and surface properties (e.g.…”
Section: Introductionsupporting
confidence: 61%
“…The ignition experiments were performed in a closed vessel with a volume of 2.2 L. This combustion facility has been previously described in detail by Boettcher et al [14], Boettcher [15] and Menon et al [16]. Briefly, the vessel inner dimensions were 114 mm x 114 mm x 171 mm.…”
Section: Combustion Vesselmentioning
confidence: 99%
“…The uniformity of surface temperature needs to be optimized and quantified to reduce uncertainties. The present study extends previous work that used a commercial glow plug as a hot surface [34][35][36][37][38][39] . To improve the surface temperature uniformity, a new cylindrical surface was developed with a unity aspect ratio of the hot surface section.…”
Section: Introductionsupporting
confidence: 85%
“…Figure 1 presents a cross-sectional view of the device. The material, stainless steel (316), corresponds to previous work using a commercial glow plug as a hot surface [34][35][36][37]39] . The stainless steel tube was centered between two 30 mm long thermally and electrically insulating quartz glass tubes to create a continuous geometric contour and to limit axial heat loss.…”
Section: Heated Cylindermentioning
confidence: 99%
“…Accidental combustion events in fuel tanks and flammable leakage zone is a major concern in aviation safety [1,2,3,4]. For example, the National Transport Safety Board investigation pointed out that the explosion of the center wing fuel tank resulting from the ignition of the flammable atmosphere in the tank as the probable cause of the flight TWA 800 accident in 1996 [5].…”
Section: Introductionmentioning
confidence: 99%